Passion Is the Gale : Emotion, Power, and the Coming of the American Revolution - Eustace, Nicole (Book collections on Project MUSE., 2008)
At the outset of the eighteenth century, many British Americans accepted the notion that virtuous sociable feelings occurred primarily among the genteel, while sinful and selfish passions remained the reflexive emotions of the masses, from lower-class white to Indians to enslaved Africans. Yet by 1776 radicals would propose a new universal model of human nature that attributed the same feelings and passions to all humankind and made common emotions the basis of natural rights. In Passion is the Gale, Nicole Eustace describes the promise and the problems of this crucial social and political of this crucial social and political transition by charting changes in emotional expression among countless ordinary men and women of British America. -- from back cover.